Modellgestützte Bewertung der Nutzung von Biokohle als Bodenzusatz in der Landwirtschaft - Radloff, Sophia (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2017)
This work provides an economic and ecological assessment of the application of biochar as soil amendment and identifies important influencing factors. Therefore, a multi-stage model including various methods, e.g. an ecosystem simulation of the soil, is developed. The assessment model is based on material and energy flow balances along the overall value chain - from biochar production to its application as soil amendment.